UNJUK KEMAMPUAN CATALYTIC CONVERTER DENGAN MATERIAL SUBSTRAT KUNINGAN ( PANDUAN CuZn ) UNTUK MEREDUKSI GAS BUANG MOTOR BENSIN - RM. Bagus lrawan; M Subri . (JURNAL LITBANG, 2005)
Abstract The aims of this experiment are firstly to conducted catalytic converter secondly, to find out to what extend Kuningan ( CuZn) as catalyst is efficient . To measure the concentration of carbon Monoxide on frame there are two conditions required. First is when the engine is on, and second is when Kuningan catalytic analyzer This experiments results in the fact that the use of Kuningan  catalytic  converter the Varian number of its cell reduces the Production of Carbon Monoxide of Premium automobile Keywords : Catalytic Converter Katalis Kuningan  Konsentrasi CO